Assessing Community Needs Among Spanish-Speaking Patients in a Free Clinic Setting - Nicole M. Clark; Jason L. Hirsch; Cecilia R. Wallace; Jonathan Zhou; August Gonzalez; Frida Calderon; Emily Bogdanski; Cameron Rodriguez; Moira Anderson; Sara Scott; Kathleen Wyne; Summit Shah (SAGE Publishing, 2024)
Introduction and Objectives: La Clínica Latina is a free clinic that strives to meet the healthcare needs of the Spanish-speaking population of Franklin County, Ohio, including metropolitan Columbus. As a student-run free clinic, care is provided each week by volunteer medical students and resident physicians under the administrative leadership of the medical student board and clinical supervision of licensed physicians. Patients served by the clinic have a multitude of chronic health conditions, which are managed by clinic volunteers through the delivery of over 1500 appointments per year. In order to better serve the rapidly growing patient population, this study describes the delivery and results of an assessment aimed at understanding the needs that are being met sufficiently at the clinic and what pitfalls still exist in the clinic's provision of care. Methods: By delivering a survey inquiring about the experiences of patients at La Clínica Latina, clinic workflow can be optimized for the provision of patient-centered care. Results: Insights collected from a convenience sample of 30 patients demonstrate mobile phone use as the primary mode of communication with clinic volunteers, previously under-appreciated musculoskeletal health concerns, longer than desired wait times after check-in, and variable experiences of health literacy by patient gender. Conclusion: By addressing each of these insights in updates to clinic workflow, La Clínica Latina may prove to become an even more useful resource to the region's growing Hispanic population.